2007
DOI: 10.1242/jcs.03459
|View full text |Cite
|
Sign up to set email alerts
|

Cellular prion protein interaction with vitronectin supports axonal growth and is compensated by integrins

Abstract: . (1992). Acetylcholine synthesis and release is enhanced by dibutyryl cyclic AMP in a neuronal cell line derived from mouse septum. J. Neurosci. 12, 793-799. Brentani, R. R. (1988

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 86 publications
4
89
0
2
Order By: Relevance
“…11 When added in excess, the RGD peptide competes for the integrin binding to ECM and probably in this specific case, for a v b 3 interaction with vitronectin present in the blood. The incubation of clone C5 (Prnp 0/0 ras/myc) with RGD peptide impaired lung retention to the levels of untreated V12 clone (Prnp 1/1 ras/ myc) (Fig.…”
Section: Prnpmentioning
confidence: 99%
See 1 more Smart Citation
“…11 When added in excess, the RGD peptide competes for the integrin binding to ECM and probably in this specific case, for a v b 3 interaction with vitronectin present in the blood. The incubation of clone C5 (Prnp 0/0 ras/myc) with RGD peptide impaired lung retention to the levels of untreated V12 clone (Prnp 1/1 ras/ myc) (Fig.…”
Section: Prnpmentioning
confidence: 99%
“…2 The association of PrP C and STI1 mediates neuronal survival and differentiation, 8 similarly the association of PrP C with laminin (LN) and vitronectin (VN) promotes neuronal adhesion and differentiation. [9][10][11] Since PrP C functions are very broad, we hypothesize that alterations in PrP C expression and/or activity are associated with pathological conditions. For instance, PrP C partners, such as those described above, are involved in the control of cellular adhesion, programmed cell death and differentiation.…”
Section: Uiccmentioning
confidence: 99%
“…42 In addition, the authors reported that the regulation of Nanog transcription by PrP involves integrin (αvβ5), a heterodimeric transmembrane protein family involved in cell adhesion, signaling, migration, differentiation and proliferation. 43 In line with these results, another report demonstrated that, during certain processes in embryogenesis, there is some redundancy in PrP interactions and the integrin signaling pathway, 10 which is crucial for mouse ES cells self-renewal regulation. 44 These results are supported further by previous studies, which revealed that integrin stimulation is related to Nanog expression, 45 and that PrP could be involved in integrin activity via E-cadherin, regulating cell adhesion.…”
Section: Prp Guides the Biology Of Tissue-specific Stem Cellsmentioning
confidence: 69%
“…8,9 For instance, the potential role of PrP in supporting axonal growth can be compensated by upregulation of integrins in PrP-knockout mice. 10 However, subsequent studies have revealed that PrP-deficient mice, after appropriate challenge, present subtle phenotypes, such as alterations in neurotransmission and synaptic plasticity, [11][12][13] hippocampal spatial memory 14 and aversive hippocampal memory in aged animals, 15 circadian rhythms 16,17 and immune responses, 18,19 as well as higher sensitivity to various stress conditions, which causes increased neuronal death. Remarkably, diverse phenotypic abnormalities were observed when PrP mutants with specific deletions in the Prnp gene were re-introduced in PrP-deficient mice.…”
Section: Prion Protein In Embryonic Developmentmentioning
confidence: 99%
“…The recent studies of PrP interactions seem to point towards interactions of PrP with extracellular proteins such as vitronectin [44] or glycosaminoglycans (heparin) and with proteins located in rafts like caveolin-1 [127] to transduct signals via the Fyn pathway. These signals could induce neuroprotection or neuritogenesis [61] or even short term and longterm memory [22].…”
Section: Prp Conversion Mediated By Other Moleculesmentioning
confidence: 99%